Automation of end-of-line systems using collaborative robots - Sawas, Mohamad (My University, 2018)
Collaborative robots have been widely used in the factories where the production lines are automated. The new industrial revolution, usually referred to as Industry 4.0, is based on the smart manufacturing, which can be implemented by means of the automation systems. Recently, the automated robotic systems have found a great interest in the factories of food and beverages since they provide a high reliability and accuracy in production lines. Furthermore, collaborative robots reduce the human labor and increase the efficiency of the line. This thesis studies the effectiveness of implementation of an automated robotic system at the End-of-Line and, shows the process of packaging and palletizing by the collaborative robots using visualization in 3D world. It also shows the representation of the collaborative robot with 6 Degree-of-Freedom using Denavit-Hartenberg method. Furthermore, it presents the appropriate layout of End-of-Line using a simulation tool of the Visual Components program and Robot Sequence Language. The collaborative robot Uiversal Robot 5 is the main element in this project. Therefore, the purpose is to simulate, analyse and implement the automation solution for End-of-Line systems in which collaborative robot Universal Robot 5 can be utilized and adapted for accomplishing the entire process. This research discusses also on the cost effectiveness of implementing automation solution at the End-of-Line and the Workplace Organization principles from perspective of World Class Manufacturing. Simulation tool is the significant part of this study, using Off-Line Programming and statistics which allow to make analysis for the joints movements of Universal Robot 5 in order to make good and sufficient utilization with a safety design to operate with max speed.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2018
Keywords: Collaborative robot; End-of-Line; Automation; Simulation; Foods and beverages; Packaging; Palletizing; Industry 4.0; WCM (World Class Manufacturing)